2021
DOI: 10.1002/advs.202004999
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Selective Ultramicroporous Carbon Membranes for Sub‐0.1 nm Organic Liquid Separation

Abstract: Liquid-phase chemical separations from complex mixtures of hydrocarbon molecules into singular components are large-scale and energy-intensive processes. Membranes with molecular specificity that efficiently separate molecules of similar size and shape can avoid phase changes, thereby reducing the energy intensity of the process. Here, forward osmosis molecular differentiation of hexane isomers through a combination of sizeand shape-based separation of molecules is demonstrated. An ultramicroporous carbon memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…This challenging separation could benefit from the low-energy approach of membranes. Nanoporous carbon membranes (i.e., carbon molecular sieve, CMS), which are derived from the thermal decomposition of polymeric materials, have demonstrated the fine separation of molecules with sub-0.1 nm size differences: gas separations for light hydrocarbons (C 2 or C 3 compounds), natural gases (N 2 /CH 4 ), and liquid hydrocarbon separations for xylene isomers or hexane isomers 5 10 . The CMS provides slit-like transport pathways for the molecules by its disordered sp 2 -hybridized graphenic layers.…”
Section: Introductionmentioning
confidence: 99%
“…This challenging separation could benefit from the low-energy approach of membranes. Nanoporous carbon membranes (i.e., carbon molecular sieve, CMS), which are derived from the thermal decomposition of polymeric materials, have demonstrated the fine separation of molecules with sub-0.1 nm size differences: gas separations for light hydrocarbons (C 2 or C 3 compounds), natural gases (N 2 /CH 4 ), and liquid hydrocarbon separations for xylene isomers or hexane isomers 5 10 . The CMS provides slit-like transport pathways for the molecules by its disordered sp 2 -hybridized graphenic layers.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al reported CMS membranes derived from 4,4′-(hexafluoroisopropylidene) diphthalic anhydride (6FDA)-based polyimide precursors for liquid-phase hexane isomers separation. The ultramicropore membranes successfully separated hexane isomers with a sub-0.1 nm size difference by employing draw solutions as driving forces [ 348 ]. Designs of flat sheet membrane material for the OSFO process have been reported in the literature, such as Ti 3 C 2 T x MXenes [ 349 ] and GO [ 350 ] nanosheets interlayered membrane.…”
Section: Applications Of Hollow Fiber Membranesmentioning
confidence: 99%
“…Carbon molecular sieves (CMS) have shown great potential as high-performance membrane materials in gas and organic solvent separation due to their thermal and chemical stability as well as scalability. Various types of precursors including polyimides , and cellulose-based polymers , have been investigated for the CMS membranes for gas separations. Recent studies have also highlighted the potential of CMS membranes for treating dissolved organics in water via an organic selective separation. , A critical advantage of CMS as a membrane material is that its pore size distribution (PSD) can be precisely engineered by altering the polymer precursors and pyrolysis conditions. CMS membranes offer tailored rates of guest molecule mobility within the microporous environment, offering the potential to address specific separation challenges encountered in wastewater remediation.…”
Section: Introductionmentioning
confidence: 99%